Jurnal PENGARUH NILAI TUKAR (KURS), JUMLAH UANG BEREDAR DAN INFLASI TERHADAP NILAI AKTIVA BERSIH REKSA DANA SYARIAH DI INDONESIA TAHUN 2015-2019 Wirman Universitas Singaperbangsa Karawang wirman@feb.unsika.ac.id: Reksa Dana Syariah di Indonesia - Wirman Wirman (Accounthink, 2020)
ABSTRACT This research was conducted to analyse and test the influence of exchange rate, the money supply and inflation on the Sharia fund net asset value in Indonesia. In this study the sampling techniques used are non probability sampling with the type of purposive sampling. The data analysis methods used in this study were classical assumption tests, hypotheses testing and multiple linear regression analyses with the help of SPSS. The results of this research show that the exchange rate, the money supply and the simultaneous inflation have significant effect on the Sharia fund's net asset value. This is evidenced by the F test results in this study, where Fcount (167,970) > Ftable (3.16) and the significance of the sig. (0.000) < 0.05, stating H0 on reject and Ha accepted. Partially, the exchange rate doesn’t have a significant effects on the value of the Sharia fund's net assets. This is evidenced by the results of the T test on this study, where t count (-0,254) > t table (2.00172), which states H0 accepted and Ha in decline. Meanwhile, the money supply and inflation have a positive and significant effect on the Sharia Fund's net asset value. This is evidenced by the results of the T test on this research, where the money supply is obtained t count (15,257) > t table (2.0017) and on inflation is obtained t count (5,086) > t table (2.0017), stating H0 in decline and Ha accepted. Keywords: exchange rate, the money supply, inflation, sharia fund net asset value. ABSTRACT This research was conducted to analyse and test the influence of exchange rate, the money supply and inflation on the Sharia fund net asset value in Indonesia. In this study the sampling techniques used are non probability sampling with the type of purposive sampling. The data analysis methods used in this study were classical assumption tests, hypotheses testing and multiple linear regression analyses with the help of SPSS. The results of this research show that the exchange rate, the money supply and the simultaneous inflation have significant effect on the Sharia fund's net asset value. This is evidenced by the F test results in this study, where Fcount (167,970) > Ftable (3.16) and the significance of the sig. (0.000) < 0.05, stating H0 on reject and Ha accepted. Partially, the exchange rate doesn’t have a significant effects on the value of the Sharia fund's net assets. This is evidenced by the results of the T test on this study, where t count (-0,254) > t table (2.00172), which states H0 accepted and Ha in decline. Meanwhile, the money supply and inflation have a positive and significant effect on the Sharia Fund's net asset value. This is evidenced by the results of the T test on this research, where the money supply is obtained t count (15,257) > t table (2.0017) and on inflation is obtained t count (5,086) > t table (2.0017), stating H0 in decline and Ha accepted. Keywords: exchange rate, the money supply, inflation, sharia fund net asset value.